NALISIS KEPUTUSAN PEMBELIAN SECARA ONLINEPADA MARKETPLACE TOKOPEDIA - Marni Dewi Yanti (2021)
Tokopedia is one of several Marketplaces in Indonesia that gives everyone, umkm and brands the opportunitu to open and develop an Online store whose services can be used for free by everyone. This study aims to determine what influences Online purchasing decisions on the The Tokopedia Marketplace, which includes services quality and E-Word of Mouth. This research uses a quantitative approach with primary data source. The sample in this study amounted to 100 respondents who were Tokopedia users using non-probability sampling techniques by means of convenience sampling. Data collection uses an equestinnaire (google form) which is distributed Online through social networks. The data analysis technique was processed using Partial Least Square (PLS). The results of data analysis show that : (1) Service Quality has a significant effect on Purchasing Decisions Online at the Tokopedia Marketplace (2) E-Word of Mouth has a significant effect on Purchasing Decisions on the Tokopedia Marketplace